Estimation Approach of Road Friction Coefficient Based on Nonlinear Least Squares - DING Xiying; LIU Rihui; CUI Ziwei; SHEN Siyao; CHENG Kailong (Kongzhi Yu Xinxi Jishu)
It proposed a kind of estimation approach for road friction coefficient based on nonlinear least squares, which has a good estimate characteristic to the steering condition. First of all, based on the structure of monorail car, two degrees of freedom vehicle lateral motion model was established, then the least squares problem was build according to the dynamics equations , at the same time it put forward a new method of iterative initial value selection. Simulation results show that the method can accurately estimate the road friction coefficient in real time under the steering condition.